Pengaruh Faktor Sikap, Norma Subjektif, Kontrol Perilaku terhadap Kebiasaan Merokok pada Atlet di UKM Bulutangkis X Surabaya - Cici Violita Dewi Cintya; Sri Widati (Universitas Airlangga, 2017)
Smoking habit can be done by all circles and professions includes badminton athletes. The purpose of this study is to determine the effect of attitude, subjective norms, and behavior control about smoking habit to athletes on the UKM Bulutangkis of X University Surabaya. This research is analytic by using cross sectional research design using total population in UKM Bulutangkis University X Surabaya. Respondents fulfilled the inclusion criteria in this study amounted to 35 atlet. Data analysis used is logistic regression. The result showed that as many as 40% athletes have smoking habit. The result of regression test showed that attitudes factor (Odds Ratio = 36), subjective norms (Odds Ratio = 15.583), and behavior control (Odds Ratio=17.333) influence smoking habits to UKM Bulutangkis of X University Surabaya is athletes. The conclusion of the research is attitude factor, subjective norm, and behavior control have positive influence to smoking habit at athlete at badminton badminton University X Surabaya. Attitudinal factors are the most positive factor in smoking. Athletes who smoke should start to reduce smoking by avoid and refuse a friend or neighborhood stimulus to smoking. Athletes who do not smoke, still maintain the habit of not smoking by motivating themselves that smoking will harm health. UKM Bulutangkis Universitas X Surabaya, should advise athletes who smoke to reduce smoking and quit smoking habit.